LEXICAL DENSITY AND GRAMMATICAL INTRICACY IN THE STUDENTS’ ENGLISH TEXTBOOK OF GRADE XI VOCATIONAL SCHOOL - Nanda Aulia Putri and Siti Aisah Ginting (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
The study analyzes about lexical density and grammatical intricacy which aim to construe the lexical density index and the grammatical intricacy index of the texts of English textbooks for eleventh grade of vocational school, to find out the highest level of lexical density and grammatical intricacy which formed in the reading texts and then both are classified based on the categories which is conducted in this study. This study was conducted by using descriptive qualitative method. The data of this study were English reading texts in Get Along with English textbook for grade eleventh vocational school published by Erlangga.The results are: there are eleven reading texts which are classified into five genres of texts; they are report text, recount text, procedure text, descriptive text and discussion text. There are seven reading texts which are classified into medium level of frequency. In addition, there are four reading texts are classified into low level of lexical density after having counted by conducting Halliday’s theory, whereas to classify grammatical intricacy index, the results are all of reading texts are included into low level of frequency by using scale zero to ten. The results imply that the reading texts may be quite comprehended by eleventh grade of vocational school students because most of reading texts are classified into medium level category with the highest indices are: (1) the LD is 4.65; (2) the GI is 4.66. It is suggested that further textbook writers to concern with the lexical density of the reading texts, and for the teachers also have to adjust the teaching materials with the genre of texts which being taught so that the students can achieve the goal of the study.